COVID-19 and Hearing: Pure Tone, Speech, and High-Frequency Audiometry - Yildirim Gökay, Nuriye; Cesur Aksoy, Gökçen; Karamert, Recep (Journal of the American Academy of Audiology, 2024)
Background Coronavirus disease 2019 (COVID-19) and its effects on hearing performance have been an interesting topic for researchers recently.Purpose The objective of this study was to assess the audiological profile of people affected by COVID-19 and also to compare them with a control group who has never had COVID-19.Research Design An experimental study.Study Sample The study group consisted of 54 participants, aged 18 to 60, who were diagnosed with COVID-19 by polymerase chain reaction and recovered at least 2 months prior to audiological assessment. The control group consisted of 60 subjects in the same age range who did not have a history of COVID-19 or hearing loss.Data Collection and Analysis Post-COVID audiological data were compared. The pre-COVID-19 audiological data of 43 subjects in the study group were also compared with their post-COVID-19 data. All participants were evaluated with pure tone audiometry, acoustic immittancemetry, speech audiometry, and high-frequency audiometry.Results Pure tone hearing thresholds, speech recognition and discrimination scores, and high-frequency hearing thresholds were all statistically different between the study and control groups (p < 0.05). There were statistically significant differences between the study group's pure tone hearing thresholds before and after COVID-19 (p < 0.05).Conclusion COVID-19 can adversely affect hearing performance. Further studies including auditory brainstem response, otoacoustic emissions, and similar cross-check tests are needed to reveal further effects of COVID-19 on hearing.
Keywords: COVID-19; hearing; high-frequency hearing loss